Texturing additive composition for silicon wafer and texturing liquid

By using polysaccharide compounds in heterojunction solar cells, the problems of suede uniformity and pyramid size regulation are solved, the photoelectric conversion efficiency and stability of solar cells are improved, and the velvet making is reduced. Time, suitable for the production of heterojunction solar cells.

CN119120024AActive Publication Date: 2024-12-13TAN KAH KEE INNOVATION LAB

Patent Information

Application Number
CN202411244426.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-05
Publication Date
2024-12-13
Estimated Expiration
2044-09-05

AI Technical Summary

Technical Problem

The existing velvet making liquid is difficult to control suede uniformity and pyramid size at the same time, affecting the photoelectric conversion efficiency and stability of heterojunction solar cells.

Method used

Develop a velvet-making additive composition containing polysaccharide compounds as nucleating agents. By adjusting their molecular weight distribution range and polydispersity index, and combining auxiliary nucleation agents, etching control agents, dispersants and surfactants, they prepare Polysaccharide compounds with narrow molecular weight distribution are used for velvet making liquids to achieve uniformity and controllable size of the distribution of suede pyramids.

Benefits of technology

The uniformity of the suede pyramid distribution is achieved, and the apparent reflectivity of the silicon wafer surface is reduced. It is suitable for amorphous silicon thin film deposition of heterojunction solar cells, which improves the photoelectric conversion efficiency and stability of the battery and reduces the fleece making time. , improves production efficiency.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005030337360000021
    Figure BDA0005030337360000021
  • Figure BDA0005030337360000041
    Figure BDA0005030337360000041
  • Figure BDA0005030337360000051
    Figure BDA0005030337360000051
Patent Text Reader

Abstract

The invention relates to a texturing additive composition for a silicon wafer and a texturing solution. The texturing additive composition comprises the following components: 0.01-7.5 wt% of a nucleating agent; 0.05 to 5.5 wt% of an etching control agent; 0.0001 to 3.5 wt% of a dispersant; 0.0 to 2.0 wt% of a surfactant; 0.0 to 5.0 wt% of a pH conditioning agent; and water. The texturing additive composition and the texturing liquid can be matched with the special thin film deposition requirement of the heterojunction solar cell, and the synergistic effect of the components in the texturing additive composition can optimize the texturing structure combination on the basis of ensuring the texturing full rate, so that the texturing pyramid distribution is uniform, and the texturing quality is improved. And the apparent reflectivity of the surface of the silicon wafer is lower. The suede structure combination is beneficial to deposition of an amorphous silicon film in the next process of the heterojunction solar cell, and meanwhile, the suede structure combination has excellent light trapping performance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of solar cell production and application, in particular to a texturing additive composition and a texturing liquid for silicon wafers. Background Art

[0002] Heterojunction solar cells are a new type of high-efficiency solar cells. They were developed by Japan's Sanyo Company by introducing thin film deposition technology into crystalline silicon solar cells. Combined with IBC (Interdigitated Back Contact) technology, heterojunction solar cells have become one of the most efficient crystalline silicon cells at present, with broad development prospects. Thin film deposition technology is the key to ensuring the photoelectric conversion efficiency and stability of heterojunction solar cells. Based on the requirements of thin film deposition technology, heterojunction solar cells have more stringent requirements on the texture of the monocrystalline silicon substrate than traditional solar cells. Monocrystalline silicon is the main material for preparing solar cells. Textured monocrystalline silicon surface can not only reduce the reflectivity of the surface, but also make light enter the cell at an angle to increase the optical path, and more effectively improve the photoelectric conversion efficiency of the cell.

[0003] Texturing is a process that uses alkaline solution to anisotropically etch different crystal planes of monocrystalline silicon to form a pyramid velvet surface on the surface of the silicon wafer. The uniformity of the velvet pyramid on the surface of crystalline silicon and the size of the pyramid have a significant impact on the subsequent amorphous silicon thin film deposition process. It is difficult for amorphous silicon thin film to be uniformly deposited at the bottom of a pyramid that is too small; and due to the effect of stress, microcracks are easily generated, resulting in a poor passivation effect. Therefore, increasing the size of the pyramid can effectively improve the open circuit voltage of silicon heterojunction solar cells. At the same time, good pyramid uniformity can improve light trapping to increase the short-circuit current of the solar cell, thereby improving the photoelectric conversion efficiency of the silicon heterojunction solar cell. In addition, since the coating processes used by different solar cell manufacturers are somewhat different, in order to obtain the best effect, the size of the velvet pyramid corresponding to different coating processes varies greatly.

[0004] Existing texturing liquids are difficult to simultaneously take into account the uniformity of the velvet surface and the regulation of different pyramid sizes. Therefore, it is very important for the development of silicon heterojunction solar cells to develop a new type of texturing additive composition to achieve the purpose of adjusting the velvet pyramid size and taking into account good velvet uniformity. Summary of the invention

[0005] The present application provides a texturing additive composition for silicon wafers, comprising the following components:

[0006]

[0007] water;

[0008] Wherein, the sum of the weight percentages of the components of the texturing additive composition is 100wt%;

[0009] The nucleating agent is a polysaccharide compound, the molecular weight distribution range of the polysaccharide compound is D1 to D2, and the polydispersity index is 1.00-1.90; wherein D2 and D1 are both within 1×10 2 -1×10 7 Daltons, and D2:D1 is (5-50):1, preferably (5-20):1.

[0010] In one embodiment, the molecular weight distribution range of the polysaccharide compound is 1×10 3 -1×10 4 Dalton; or

[0011] The molecular weight distribution range of the polysaccharide compound is 1×10 4 -1×10 5 Dalton; or

[0012] The molecular weight distribution range of the polysaccharide compound is 1×10 5 -1×10 6 Dalton; or

[0013] The molecular weight distribution range of the polysaccharide compound is 1×10 6 -1×10 7 Dalton.

[0014] In one embodiment, the polysaccharide compound is selected from one or more of carboxymethyl cellulose, hydroxyethyl cellulose, sodium carboxymethyl starch, water-soluble starch, xanthan gum, carrageenan, locust bean gum, sesbania gum and carrageenan;

[0015] Preferably, the polysaccharide compound is selected from one or more of sodium carboxymethyl starch, carrageenan, locust bean gum and xanthan gum.

[0016] In one embodiment, the polysaccharide compound is prepared as follows:

[0017] The polysaccharide raw material is hydrolyzed under acidic conditions, and then the molecular weight distribution range of the hydrolyzed polysaccharide raw material is narrowed to obtain the polysaccharide compound.

[0018] In one embodiment, the molecular weight distribution range is narrowed by dialysis, and the dialysis comprises:

[0019] The first dialysis was performed with a first dialysis bag having a molecular weight cut-off of D1, and the second dialysis was performed with a second dialysis bag having a molecular weight cut-off of D2.

[0020] In one embodiment, D1 is located at 1×102 -1×10 5 Dalton, D2 is located at 1×10 3 -1×10 6 Dalton between.

[0021] In one embodiment, the texturing additive composition further comprises an auxiliary nucleating agent in an amount of 0.00001-3.5 wt %, based on the total weight of the texturing additive composition.

[0022] In one embodiment, the auxiliary nucleating agent is selected from one or more of sodium silicate, sodium chloride, potassium chloride, sodium carbonate, potassium carbonate, lignin and its derivatives, hematoxylin and its derivatives, and humic acid and its extracts.

[0023] In one embodiment, the etching control agent is selected from one or more of polyethylene glycol, polypropylene glycol, polyethylene glycol monomethyl ether, polyethylene glycol dimethyl ether, polyethylene imine, polyvinyl alcohol, cyclohexanediol, 3-methyl-1,5-pentanediol, N-methylpyrrolidone, polyvinylpyrrolidone, chitosan, chitosan oligosaccharide and sorbitol; preferably, the etching control agent is selected from one or more of polyethylene glycol monomethyl ether, 3-methyl-1,5-pentanediol, polyethylene imine and chitosan oligosaccharide.

[0024] In one embodiment, the dispersant is selected from one or more of sodium lactate, sodium benzoate, sodium tripolyphosphate, sodium hexametaphosphate, sodium 5-nitroguaiacol, sodium citrate, sodium gluconate, sodium methylene bisnaphthalene sulfonate, sodium carbonate, sodium acetate and sodium tartrate; preferably, the dispersant is selected from one or more of sodium hexametaphosphate, sodium citrate and sodium benzoate.

[0025] In one embodiment, the surfactant is selected from one or more of disodium lauryl sulfosuccinate, fatty alcohol polyoxyethylene ether, fatty acid methyl ester ethoxylate, fatty acid methyl ester ethoxylate sulfonate, disodium coconut oil monoethanolamide sulfosuccinate, sodium dodecyl sulfate, sodium dodecylbenzene sulfonate and sodium oleate; preferably, the surfactant is selected from one or more of fatty alcohol polyoxyethylene ether, sodium dodecyl sulfate and sodium dodecylbenzene sulfonate.

[0026] In one embodiment, the pH adjuster is selected from one or more of sodium hydroxide, potassium hydroxide, propionic acid, acetic acid, formic acid, maleic acid, maleic anhydride, lauryl ether phosphate, cocoyl monoethanolamide, cocamidopropyl betaine and cocamidopropyl hydroxysulfonate; preferably, the pH adjuster is selected from one or more of sodium hydroxide, acetic acid and lauryl ether phosphate.

[0027] The present application also provides a texturing liquid, which comprises an alkali, the texturing additive composition of the present application and water.

[0028] In one embodiment, the base is an inorganic base and / or an organic base; preferably, the inorganic base is KOH and / or NaOH, and the organic base is tetramethylguanidine and / or tetraethylammonium hydroxide.

[0029] In one embodiment, the amount of the texturing additive composition is 0.05-1.5 wt %, based on the total weight of the texturing liquid;

[0030] The amount of the alkali is 0.5-5.5 wt %, based on the total weight of the texturing solution.

[0031] The texturing additive composition and texturing liquid of the present application can match the special thin film deposition requirements of heterojunction solar cells. The synergistic effect of the various components in the texturing additive composition can optimize the velvet structure combination on the basis of ensuring the velvet coverage rate, so that the velvet pyramids are evenly distributed, the velvet uniformity is good, and the apparent reflectivity of the silicon wafer surface is lower. This velvet structure combination is conducive to the deposition of amorphous silicon thin films in the next process of heterojunction solar cells, and at the same time has excellent light trapping properties, thereby obtaining a stable and reliable heterojunction solar cell. BRIEF DESCRIPTION OF THE DRAWINGS

[0032] Figure 1 The SEM image of the textured surface of the silicon wafer obtained in Example 1 is shown;

[0033] Figure 2 The SEM image of the textured surface of the silicon wafer obtained in Example 2 is shown;

[0034] Figure 3 The SEM picture of the textured surface of the silicon wafer obtained in Example 3 is shown;

[0035] Figure 4 The SEM picture of the textured surface of the silicon wafer obtained in Example 4 is shown;

[0036] Figure 5 The SEM picture of the textured surface of the silicon wafer obtained in Comparative Example 1 is shown;

[0037] Figure 6 The SEM picture of the textured surface of the silicon wafer obtained in Comparative Example 2 is shown;

[0038] Figure 7 The SEM image of the textured surface of the silicon wafer obtained in Example 5 is shown;

[0039] Figure 8 The SEM picture of the textured surface of the silicon wafer obtained in Example 6 is shown;

[0040] Fig. 9 The SEM picture of the textured surface of the silicon wafer obtained in Example 7 is shown;

[0041] Fig.10 The molecular weight distribution curve of the xanthan gum in Comparative Example 1 is shown;

[0042] Fig.11 The molecular weight distribution curve of xanthan gum obtained by preliminary hydrolysis in Comparative Example 2 is shown;

[0043] Fig.12 The molecular weight distribution curve of the xanthan gum obtained in Example 1 is shown. DETAILED DESCRIPTION

[0044] The present application is further described in detail below through the accompanying drawings and embodiments. Through these descriptions, the characteristics and advantages of the present application will become clearer and more specific.

[0045] The word "exemplary" is used exclusively herein to mean "serving as an example, embodiment, or illustration." Any embodiment described herein as "exemplary" is not necessarily to be construed as preferred or advantageous over other embodiments. Although various aspects of the embodiments are shown in the drawings, the drawings are not necessarily drawn to scale unless otherwise noted.

[0046] In addition, the technical features involved in different embodiments of the present application described below can be combined with each other as long as they do not conflict with each other.

[0047] The present application provides a texturing additive composition for silicon wafers, comprising the following components:

[0048]

[0049]

[0050] water;

[0051] Wherein, the sum of the weight percentages of the components of the texturing additive composition is 100wt%;

[0052] The nucleating agent is a polysaccharide compound, the molecular weight distribution range of the polysaccharide compound is D1 to D2, and the polydispersity index is 1.00-1.90; wherein D2 and D1 are both within 1×10 2 -1×10 7 Daltons, and D2:D1 is (5-50):1, preferably (5-20):1.

[0053] In the present application, "molecular weight distribution range is D1 to D2" means that in the molecular weight distribution curve of polysaccharide compounds, the total mass percentage of molecules with molecular weight lower than D1 is lower than 10%, even lower than 5%, even lower than 1%; the total mass percentage of molecules with molecular weight higher than D2 is also lower than 10%, even lower than 5%, even lower than 1%. That is, the total mass percentage of molecules with molecular weight between D1 and D2 accounts for more than 85%, even more than 90%, even more than 95% of all molecules.

[0054] The polysaccharide compound used as the nucleating agent of the present application has a narrow molecular weight distribution (polydispersity index) and a relatively small molecular weight distribution range. The inventors of the present application unexpectedly discovered that when a polysaccharide compound with a relatively narrow molecular weight distribution range is used as a texturing liquid for a nucleating agent to texturize a single crystal silicon wafer, a pyramid velvet with very good velvet uniformity can be obtained. Moreover, by adjusting the values ​​of D1 and D2 in the molecular weight distribution range, the size of the pyramid velvet can also be adjusted, that is: when D1 and D2 are larger, a smaller-sized pyramid velvet is obtained; when D1 and D2 are smaller, a larger-sized pyramid velvet can be obtained. Thus, the upper and lower limits of the appropriate molecular weight distribution range can be selected according to different needs.

[0055] In one embodiment, the molecular weight distribution range of the polysaccharide compound is 1×10 3 -1×10 4 ; Or, the molecular weight distribution range of the polysaccharide compound is 1×10 4 -1×10 5 ; Or, the molecular weight distribution range of the polysaccharide compound is 1×10 5 -1×10 6 ; Or, the molecular weight distribution range of the polysaccharide compound is 1×10 6 -1×10 7 In this molecular weight distribution range, the polysaccharide compound has a unimodal molecular weight distribution curve, and the polydispersity index PDI is relatively narrow, which is 1.00-1.90, such as 1.05-1.70, such as 1.10-1.60.

[0056] The nucleating agent is a polysaccharide compound with a specific molecular weight distribution range and molecular weight distribution. The structural characteristics of this type of compound are high molecular weight compounds with multiple hydroxyl groups. During the texturing process, the hydroxyl groups are adsorbed on the surface of the silicon wafer, which can hinder the OH in the alkaline solution. - The ions react with the silicon wafer, forming fuzzy spots at the adsorption sites.

[0057] In one embodiment, the polysaccharide compound is selected from one or more of carboxymethyl cellulose, hydroxyethyl cellulose, sodium carboxymethyl starch, water-soluble starch, xanthan gum, carrageenan, locust bean gum, sesbania gum and carrageenan.

[0058] Preferably, the polysaccharide compound is selected from one or more of sodium carboxymethyl starch, carrageenan, locust bean gum and xanthan gum.

[0059] In one embodiment, the polysaccharide compound used in the present application can be prepared as follows:

[0060] The polysaccharide raw material is hydrolyzed under acidic conditions, and then the molecular weight distribution range of the hydrolyzed polysaccharide raw material is narrowed to obtain the polysaccharide compound.

[0061] The polysaccharide raw materials used in this application are all commercially available USP grade or ACS grade. After the applicant purchases the polysaccharide raw materials, the molecular weight distribution is measured. The molecular weight distribution range of the polysaccharide raw materials meets the upper limit of not less than 1×10 7 Dalton, it can be ensured that the polysaccharide compound can be prepared by the above method.

[0062] The preliminary hydrolysis process can be carried out as follows: the nucleating agent raw material (polysaccharide compound raw material) is completely dissolved in an inorganic strong acid, such as an inorganic strong acid with a concentration of 0.01-1.0 mol / L (such as hydrochloric acid, sulfuric acid, etc.), and heated at a certain temperature (such as 50-80°C) for a period of time (such as 1-24h). After hydrolysis, the solution is adjusted to a neutral pH with an alkali such as NaOH solution or KOH solution.

[0063] After the initial hydrolysis, the molecular weight distribution range is narrowed to obtain the polysaccharide compound used as a nucleating agent of the present application. The molecular weight distribution range can be narrowed by separation means such as extraction, column chromatography, electrophoresis, centrifugation and recrystallization. Dialysis can be performed by a single dialysis process, and the polysaccharide compound used as a nucleating agent of the present application is retained in the dialysis bag after dialysis.

[0064] Two dialysis processes can also be performed: the first dialysis is performed with the first dialysis bag with a molecular weight cutoff of D1 and the second dialysis is performed with the second dialysis bag with a molecular weight cutoff of D2. It should be noted that the order of performing the first dialysis with the first dialysis bag with a molecular weight cutoff of D1 and performing the second dialysis with the second dialysis bag with a molecular weight cutoff of D2 can be changed. That is, the first dialysis can be performed with the first dialysis bag with a molecular weight cutoff of D1, and then the solution in the first dialysis bag is transferred to the second dialysis bag with a molecular weight cutoff of D2 for the second dialysis. It is also possible to first perform dialysis with the second dialysis bag with a molecular weight cutoff of D2, and then transfer the solution outside the second dialysis bag to the first dialysis bag with a molecular weight cutoff of D1 for dialysis.

[0065] In one embodiment, D1 is located at 1×10 2 -1×10 5 Dalton, D2 is located at 1×10 3 -1×10 6 Dalton between.

[0066] In the texturing additive composition of the present application, the amount of the nucleating agent is 0.01-7.5 wt %, such as 0.1-5.0 wt %, such as 0.2-4.0 wt %, based on the total weight of the texturing additive composition.

[0067] In one embodiment, the texturing additive composition further includes an auxiliary nucleating agent in an amount of 0.00001-3.5wt%, for example, 0.05-3wt%, for example, 0.1-2wt%; based on the total weight of the texturing additive composition. The auxiliary nucleating agent is selected from one or more of sodium silicate, sodium chloride, potassium chloride, sodium carbonate, potassium carbonate, lignin and its derivatives, hematoxylin and its derivatives, and humic acid and its extracts. The function of the auxiliary nucleating agent is to help the nucleating agent be more evenly distributed on the surface of the silicon wafer and improve the nucleation rate.

[0068] In one embodiment, the etching control agent is selected from one or more of polyethylene glycol, polypropylene glycol, polyethylene glycol monomethyl ether, polyethylene glycol dimethyl ether, polyethylene imine, polyvinyl alcohol, cyclohexanediol, 3-methyl-1,5-pentanediol, N-methylpyrrolidone, polyvinylpyrrolidone, chitosan, chitosan oligosaccharides and sorbitol; preferably, the etching control agent is selected from one or more of polyethylene glycol monomethyl ether, 3-methyl-1,5-pentanediol, polyethylene imine and chitosan oligosaccharides. The function of the etching control agent is to adjust the corrosion rate of the alkaline solution on the silicon wafer, which helps to anisotropically etch the single crystal silicon wafer to obtain a velvet pyramid structure. In the texturing additive composition of the present application, the amount of the etching control agent is 0.05-5.5wt%, such as 0.1-5.0wt%, such as 0.2-2.0wt%, based on the total weight of the texturing additive composition.

[0069] In one embodiment, the dispersant is selected from one or more of sodium lactate, sodium benzoate, sodium tripolyphosphate, sodium hexametaphosphate, sodium 5-nitroguaiacol, sodium citrate, sodium gluconate, sodium methylene bis naphthalene sulfonate, sodium carbonate, sodium acetate and sodium tartrate; preferably, the dispersant is selected from one or more of sodium hexametaphosphate, sodium citrate and sodium benzoate. In the texturing additive composition of the present application, the amount of the dispersant is 0.0001-3.5wt%, for example, 0.05-3.0wt%, for example, 0.1-2.5wt%, for example, 0.2-2.0wt%, based on the total weight of the texturing additive composition.

[0070] In one embodiment, the texturing additive composition of the present application may further contain a surfactant. The surfactant is selected from one or more of lauryl sulfosuccinate, fatty alcohol polyoxyethylene ether, fatty acid methyl ester ethoxylate, fatty acid methyl ester ethoxylate sulfonate, coconut oil monoethanolamide sulfosuccinate disodium, sodium dodecyl sulfate, sodium dodecylbenzene sulfonate and sodium oleate; preferably, the surfactant is selected from one or more of fatty alcohol polyoxyethylene ether, sodium dodecyl sulfate and sodium dodecylbenzene sulfonate. In the texturing additive composition of the present application, the amount of the surfactant is 0.0-2.0wt%, for example, 0.01-1.5wt%, or 0.02-1.0wt%, based on the total weight of the texturing additive composition.

[0071] In one embodiment, the texturing additive composition of the present application may further contain a pH adjuster. The pH adjuster is selected from one or more of sodium hydroxide, potassium hydroxide, propionic acid, acetic acid, formic acid, maleic acid, maleic anhydride, lauryl alcohol ether phosphate, cocoyl monoethanolamide, cocamidopropyl betaine and cocamidopropyl hydroxysulfonyl betaine; preferably, the pH adjuster is selected from one or more of sodium hydroxide, acetic acid and lauryl alcohol ether phosphate. In the texturing additive composition of the present application, the amount of the pH adjuster is 0.0-5.0wt%, for example, 0.005-4.0wt%, 0.01-3.0wt%, 0.02-1.0wt%, based on the total weight of the texturing additive composition.

[0072] As mentioned above, the existing texturing technology cannot meet the needs of cleaning and texturing of heterojunction solar cells. Specifically, the pyramid size of the velvet surface of the solar cell obtained by the texturing liquid of the conventional silicon wafer texturing additive composition is small, and the uniformity of the velvet pyramid is poor (the size of the velvet pyramid is generally 0.8-2μm, and the average size is less than 1.5μm), which is not conducive to the deposition of amorphous silicon thin film, thereby affecting the photoelectric conversion efficiency and stability of the heterojunction solar cell; and it is difficult to take into account the uniformity of the velvet surface and the regulation of different pyramid sizes at the same time. Second, the etching time of the existing texturing process is relatively long. For example, in patent CN102330155A, the texturing time is greater than 750s, which is not conducive to improving production efficiency and cannot meet the needs of silicon heterojunction solar cell production and development. Third, the texturing liquid using the conventional texturing additive composition has strong adsorption of the components on the silicon wafer surface. After the texturing is completed, the TOC value (Total Organic Carbon) on the silicon wafer surface is high, which will reduce the photoelectric conversion efficiency of the solar cell and affect its stability and reliability.

[0073] The texturing additive composition and texturing liquid of the present application can match the special thin film deposition requirements of heterojunction solar cells. The synergistic effect of the various components of the texturing additive composition optimizes the combination of velvet structures on the basis of ensuring the velvet coverage rate, so that the pyramids are evenly distributed, the velvet uniformity is good, and the apparent reflectivity of the silicon wafer surface is lower. This velvet structure combination is conducive to the deposition of amorphous silicon thin films in the next step of the heterojunction solar cell process, and at the same time has excellent light trapping properties, thereby obtaining a stable and reliable heterojunction solar cell.

[0074] By adjusting the different molecular weight distribution ranges of the nucleating agent, the pyramid size of the velvet surface can be regulated during texturing, and small, medium and large pyramids can be obtained. The average size of the small pyramid is about 1.4μm, the average size of the medium pyramid is about 2.3μm, and the average size of the large pyramid is 3.2μm. Different pyramid velvet sizes can match different solar cell coating processes and enhance the application range of the texturing additive composition.

[0075] The components in the texturing additive composition of the present application are highly soluble in water and have low adsorption effects on the surface of silicon wafers, so that the components of the additive composition are easy to clean and the TOC value of the silicon wafer surface after the cleaning step is reduced.

[0076] When the texturing liquid containing the texturing additive composition of the present application is used for texturing, the texturing time required at 75-82°C is within 500s, and the shortest can be 400s, while the texturing time required by the existing heterojunction solar cell texturing liquid is on average more than 500s. The application of the texturing additive composition can reduce the texturing time, improve production efficiency, and further reduce the production cost of heterojunction solar cells.

[0077] The present application also provides a texturing liquid, which comprises an alkali, the texturing additive composition of the present application and water.

[0078] In one embodiment, the base is an inorganic base and / or an organic base; preferably, the inorganic base is KOH and / or NaOH, and the organic base is tetramethylguanidine and / or tetraethylammonium hydroxide.

[0079] In one embodiment, the amount of the texturing additive composition is 0.05-1.5 wt %, based on the total weight of the texturing liquid;

[0080] The amount of the alkali is 0.5-5.5 wt %, based on the total weight of the texturing solution.

[0081] The texturing liquid can be prepared as follows: in a texturing tank, a certain mass of inorganic alkali / organic alkali is dissolved in ultrapure water to prepare an alkali solution with a mass concentration of 0.5-5.5wt%; then the texturing additive composition of the present application is added to the prepared alkali solution, the content of the texturing additive composition is 0.15-1.5wt% (based on the total weight of the texturing liquid), and the texturing liquid is obtained by stirring evenly.

[0082] In the present application, the above-mentioned silicon wafer can be N-type single crystal silicon or P-type single crystal silicon, etc.

[0083] Comparative Example 1

[0084] To make the monocrystalline silicon wafer texture, the following process steps are taken:

[0085] 1) Preparation of the texturing additive composition: 1.5 parts of xanthan gum raw material (USP grade, purchased and tested with a molecular weight distribution range of 1×10 4 -1×10 7 , molecular weight less than 10 4 The molecules account for 1% of the total molecular mass and have a molecular weight higher than 10 7 The molecules account for 0.1% of the total molecular mass. For the molecular weight distribution curve, see Fig.10 ; number average molecular weight is 162395; polydispersity index is 3.00; no additional treatment is performed), 0.1 parts of humic acid, 1.0 parts of polyethylene glycol monomethyl ether, 0.3 parts of sodium 5-nitroguaiacol, 0.2 parts of sodium dodecyl sulfate, 0.05 parts of sodium hydroxide, 96.85 parts of ultrapure water are added to obtain a texturing additive composition.

[0086] 2) Preparation of texturing liquid: dissolve 100 parts of KOH in 6900 parts of ultrapure water to obtain an alkaline solution; add 28 parts of the texturing additive composition prepared in step 1) to the alkaline solution to obtain a texturing liquid.

[0087] 3) Silicon wafer texturing: Take a clean silicon wafer and place it into the texturing solution prepared in step 2) heated to 82°C and etch for 480 seconds.

[0088] 4) Silicon wafer cleaning: The silicon wafer after texturing in step 3) is cleaned with deionized water, and the deionized water on the surface of the silicon wafer is blown dry with high-purity nitrogen gas.

[0089] Figure 5 The SEM picture of the textured surface of the silicon wafer obtained in Comparative Example 1 is shown, and the textured surface is not fully covered and cannot be completely textured.

[0090] Comparative Example 2

[0091] The difference between this comparative example and comparative example 1 is step 1), which is specifically:

[0092] The xanthan gum raw material in Comparative Example 1 was pretreated, that is, the xanthan gum was completely dissolved in a 0.05 mol / L HCl solution, and heated at 80°C for 6 h for preliminary hydrolysis. After the hydrolysis was completed, NaOH was added to adjust the solution to neutrality to obtain a preliminary hydrolyzed xanthan gum solution, which was then concentrated, washed, and dried to obtain a preliminary hydrolyzed xanthan gum (the molecular weight distribution range of the test was 1×10 3 -1×10 7 , molecular weight less than 10 3 The molecules account for 3% of the total molecular mass and have a molecular weight higher than 10 7 The molecules account for 0.1% of the total molecular mass. For the molecular weight distribution curve, see Fig.11 ; polydispersity index 4.05).

[0093] Prepare a texturing additive composition: add 96.85 parts of ultrapure water to 1.5 parts of preliminarily hydrolyzed xanthan gum, 0.1 part of humic acid, 1.0 part of polyethylene glycol monomethyl ether, 0.3 part of sodium 5-nitroguaiacol, 0.2 part of sodium dodecyl sulfate, and 0.05 part of sodium hydroxide to obtain a texturing additive composition.

[0094] Figure 6 The SEM picture of the textured surface of the silicon wafer obtained in Comparative Example 2 is shown, and the pyramid sizes are unevenly distributed and the texture uniformity is extremely poor.

[0095] Example 1

[0096] The difference between this embodiment 1 and comparative example 2 is step 1), which is specifically:

[0097] The xanthan gum solution preliminarily hydrolyzed in Comparative Example 2 was dialyzed by placing the preliminarily hydrolyzed xanthan gum solution on a dialysis plate with a molecular weight cutoff of 1×10 5 Dalton's first dialysis bag was placed in a beaker with 1.5L ultrapure water for dialysis separation. After the dialysis was completed, the solution in the first dialysis bag was transferred to a beaker with a molecular weight cutoff of 1×10 6 Dalton's second dialysis bag was placed in a beaker with 1.5 L of ultrapure water for secondary dialysis separation. After the completion of the dialysis solution, the xanthan gum (the molecular weight distribution range of the test result is 1×10 5 -1×10 6 , molecular weight less than 10 5 The molecules account for 1% of the total molecular mass and have a molecular weight higher than 10 6 The molecules account for 3% of the total molecular mass. For the molecular weight distribution curve, see Fig.12 ; polydispersity index PDI is 1.31).

[0098] Prepare a texturing additive composition: add 96.85 parts of ultrapure water to 1.5 parts of xanthan gum obtained as above, 0.1 part of humic acid, 1.0 part of polyethylene glycol monomethyl ether, 0.3 parts of sodium 5-nitroguaiacol, 0.2 parts of sodium dodecyl sulfate, and 0.05 parts of sodium hydroxide to obtain a texturing additive composition.

[0099] Figure 1 The SEM picture of the textured surface of the silicon wafer obtained in Example 1 is shown. Compared with Comparative Example 1, the average pyramid size is larger, the texture uniformity is better, the reflectivity is lower, and the TOC value is lower than that of Comparative Example 1.

[0100] Example 2

[0101] The difference between this embodiment and embodiment 1 lies in step 1), which is specifically:

[0102] The molecular weight cut-off of the first dialysis bag in step 1) is 1×10 4 Dalton, the molecular weight cut-off of the second dialysis bag is 1×10 5 Dalton. The molecular weight distribution range of the obtained xanthan gum is 1×10 4 -1×10 5 , polydispersity index 1.22.

[0103] Figure 2 The SEM picture of the velvet surface after velveting obtained in Example 2 is shown, indicating that by adjusting the molecular weight of the nucleating agent, a large-sized pyramid velvet surface is obtained, and the velvet surface uniformity is better.

[0104] Example 3

[0105] The difference between this embodiment and embodiment 1 lies in step 1), which is specifically:

[0106] In step 1), only the molecular weight cut-off of 1×10 6 Dalton dialysis bag for one dialysis. The molecular weight distribution range of the obtained xanthan gum is 1×10 6 -1×10 7 , polydispersity index 1.26.

[0107] Figure 3 The SEM picture of the textured surface of the silicon wafer obtained in Example 3 is shown, indicating that by adjusting the molecular weight of the nucleating agent, a small-sized pyramid texture can be obtained, and the texture uniformity is better.

[0108] Example 4

[0109] The difference between this embodiment and embodiment 1 lies in step 1), which is specifically:

[0110] The xanthan gum raw material in step 1) was replaced with carboxymethyl cellulose raw material (commercially available ACS grade, the molecular weight distribution range was 1×10 3 -1×10 7 , polydispersity index is 4.33), after preliminary hydrolysis, dialysis, concentration, washing and drying, the molecular weight distribution range of the obtained carboxymethyl cellulose is 1×10 5 -1×10 6 , polydispersity index 1.35.

[0111] Preparation of a texturing additive composition: Add 97.98 parts of ultrapure water to 0.6 parts of the carboxymethyl cellulose obtained as above, 0.4 parts of hematoxylin, 0.5 parts of 3-methyl-1,5-pentanediol, 0.4 parts of sodium benzoate, 0.1 parts of sodium dodecyl sulfate, and 0.02 parts of maleic anhydride to obtain a texturing additive composition.

[0112] Figure 4 The SEM picture of the texturing surface of the silicon wafer obtained in Example 4 is shown, indicating that by adjusting the content of the specific molecular weight and combining with a suitable auxiliary nucleating agent and dispersant, a texturing additive with better texturing uniformity can be obtained.

[0113] Example 5

[0114] The difference between this embodiment and embodiment 1 lies in step 1), which is specifically:

[0115] The xanthan gum raw material in step 1) was replaced with sodium carboxymethyl starch raw material (commercially available ACS grade, the molecular weight distribution range was 1×10 3 -1×10 7 , polydispersity index is 2.01), after preliminary hydrolysis, dialysis, concentration, washing and drying, the molecular weight distribution range of the obtained sodium carboxymethyl starch is 1×10 3 -1×10 4 , polydispersity index 1.15.

[0116] Preparation of a texturing additive composition: Add 97.78 parts of ultrapure water to 0.6 parts of sodium carboxymethyl starch obtained as above, 0.1 parts of alkaline lignin, 1.0 parts of polyethylene glycol, 0.4 parts of sodium benzoate, 0.1 parts of sodium oleate, and 0.02 parts of maleic anhydride to obtain a texturing additive composition.

[0117] Figure 7 The SEM picture of the textured surface of the silicon wafer obtained in Example 5 is shown, indicating that by adjusting the molecular weight of the nucleating agent, a large-sized pyramid texture can be obtained, and the texture uniformity is excellent.

[0118] Example 6

[0119] The difference between this embodiment and embodiment 1 lies in step 1), which is specifically:

[0120] The xanthan gum raw material in step 1) was replaced with carrageenan raw material (commercially available ACS grade, the molecular weight distribution range was 1×10 4 -1×10 7 , polydispersity index is 2.35), after preliminary hydrolysis, dialysis, concentration, washing and drying, the molecular weight distribution range of the obtained carrageenan is 1×10 4 -1×10 5 , polydispersity index 1.21.

[0121] Preparation of a texturing additive composition: Add 97.4 parts of ultrapure water to 1.0 part of the carrageenan obtained as above, 0.6 part of sodium carbonate, 1.0 part of polypropylene glycol, 0.4 part of sodium citrate, and 0.2 part of sodium dodecylbenzene sulfonate to obtain a texturing additive composition.

[0122] Figure 8 The SEM picture of the textured surface of the silicon wafer obtained in Example 6 is shown, indicating that by adjusting the molecular weight of the nucleating agent, a medium-sized pyramid texture surface can be obtained, and the texture surface uniformity is excellent.

[0123] Example 7

[0124] The difference between this embodiment and embodiment 1 lies in step 1), which is specifically:

[0125] The xanthan gum raw material in step 1) was replaced with sesbania gum raw material (commercially available ACS grade, the molecular weight distribution range was 1×10 3 -1×10 6 , polydispersity index is 2.35), and after preliminary hydrolysis, dialysis, concentration, washing and drying, the molecular weight distribution range of the obtained sesbania gum is 1×10 5 -1×10 6 , polydispersity index 1.38.

[0126] Preparation of a texturing additive composition: Add 97.88 parts of ultrapure water to 0.3 parts of sesbania gum obtained as above, 0.6 parts of sodium carbonate, 0.8 parts of chitosan oligosaccharide, 0.4 parts of sodium hexametaphosphate, and 0.02 parts of coconut acid monoethanolamide to obtain a texturing additive composition.

[0127] Fig. 9 The SEM picture of the textured surface of the silicon wafer obtained in Example 7 is shown, indicating that by adjusting the molecular weight of the nucleating agent, a small-sized pyramid texture can be obtained, and the texture uniformity is excellent.

[0128] The average pile size (obtained using an electron microscope), reflectivity (obtained using a D8 reflectivity tester) and TOC value (obtained using a total organic carbon analyzer) of the above comparative examples and embodiments were measured. The results are shown in Table 1.

[0129] Table 1

[0130] Average pile size (μm) Reflectivity(%) <![CDATA[TOC(ng / cm 2 )]]> Example 1 2.3 10.5 65 Example 2 3.2 11.8 58 Example 3 1.4 9.5 78 Example 4 2.5 10.9 46 Example 5 3.8 12.6 55 Example 6 2.8 11.2 62 Example 7 1.7 10.1 74 Comparative Example 1 / (Not fully covered) 21.7 89 Comparative Example 2 1.1 14.2 72

[0131] The results show that by adjusting the molecular weight of the nucleating agent, velvet with different pyramid sizes can be obtained on the surface of the silicon wafer. The silicon wafer obtained by the preferred nucleating agent has the advantages of adjustable velvet size, good uniformity, and stronger ability to remove organic pollution on the silicon wafer surface than the current better texturing additive composition.

[0132] The present application has been described above in conjunction with preferred embodiments, which are merely examples and serve as illustrative purposes. On this basis, various combinations, replacements and improvements may be made to the present application, all of which fall within the scope of protection of the present application.

Claims

1. A texturing additive composition for silicon wafers, comprising the following components: in, The sum of the weight percentages of the components of the texturing additive composition is 100wt%; The nucleating agent is a polysaccharide compound, the molecular weight distribution range of the polysaccharide compound is D1 to D2, and the polydispersity index is 1.00-1.90; wherein D2 and D1 are both within 1×10 2 -1×10 7 Daltons, and D2:D1 is (5-50):1, preferably (5-20):

1.

2. The texturing additive composition according to claim 1, in, The molecular weight distribution range of the polysaccharide compound is 1×10 3 -1×10 4 Dalton; or, The molecular weight distribution range of the polysaccharide compound is 1×10 4 -1×10 5 Dalton; or The molecular weight distribution range of the polysaccharide compound is 1×10 5 -1×10 6 Dalton; or The molecular weight distribution range of the polysaccharide compound is 1×10 6 -1×10 7 Dalton.

3. The texturing additive composition according to claim 1, in, The polysaccharide compound is selected from one or more of carboxymethyl cellulose, hydroxyethyl cellulose, sodium carboxymethyl starch, water-soluble starch, xanthan gum, carrageenan, locust bean gum, sesbania gum and carrageenan; Preferably, the polysaccharide compound is selected from one or more of sodium carboxymethyl starch, carrageenan, locust bean gum and xanthan gum.

4. The texturing additive composition according to claim 1, in, The polysaccharide compound is prepared as follows: The polysaccharide raw material is hydrolyzed under acidic conditions, and then the molecular weight distribution range of the hydrolyzed polysaccharide raw material is narrowed to obtain the polysaccharide compound.

5. The texturing additive composition according to claim 4, in, The molecular weight distribution range is narrowed down to dialysis, and the dialysis comprises: The first dialysis was performed with a first dialysis bag having a molecular weight cut-off of D1, and the second dialysis was performed with a second dialysis bag having a molecular weight cut-off of D2.

6. The texturing additive composition according to claim 5, in, D1 is located at 1×10 2 -1×10 5 Dalton, D2 is located at 1×10 3 -1×10 6 Dalton between.

7. The texturing additive composition according to claim 1, in, The texturing additive composition further includes an auxiliary nucleating agent in an amount of 0.00001-3.5 wt %, based on the total weight of the texturing additive composition.

8. The texturing additive composition according to claim 7, in, The auxiliary nucleating agent is selected from one or more of sodium silicate, sodium chloride, potassium chloride, sodium carbonate, potassium carbonate, lignin and its derivatives, hematoxylin and its derivatives, and humic acid and its extracts.

9. The texturing additive composition according to claim 1, in, The etching control agent is selected from one or more of polyethylene glycol, polypropylene glycol, polyethylene glycol monomethyl ether, polyethylene glycol dimethyl ether, polyethylene imine, polyvinyl alcohol, cyclohexanediol, 3-methyl-1,5-pentanediol, N-methylpyrrolidone, polyvinylpyrrolidone, chitosan, chitosan oligosaccharide and sorbitol; preferably, the etching control agent is selected from one or more of polyethylene glycol monomethyl ether, 3-methyl-1,5-pentanediol, polyethylene imine and chitosan oligosaccharide.

10. The texturing additive composition according to claim 1, in, The dispersant is selected from one or more of sodium lactate, sodium benzoate, sodium tripolyphosphate, sodium hexametaphosphate, sodium 5-nitroguaiacol, sodium citrate, sodium gluconate, sodium methylene bisnaphthalene sulfonate, sodium carbonate, sodium acetate and sodium tartrate; preferably, the dispersant is selected from one or more of sodium hexametaphosphate, sodium citrate and sodium benzoate.

11. The texturing additive composition according to claim 1, in, The surfactant is selected from one or more of disodium lauryl sulfosuccinate, fatty alcohol polyoxyethylene ether, fatty acid methyl ester ethoxylate, fatty acid methyl ester ethoxylate sulfonate, disodium coconut oil monoethanolamide sulfosuccinate, sodium dodecyl sulfate, sodium dodecylbenzene sulfonate and sodium oleate; preferably, the surfactant is selected from one or more of fatty alcohol polyoxyethylene ether, sodium dodecyl sulfate and sodium dodecylbenzene sulfonate.

12. The texturing additive composition according to claim 1, in, The pH adjuster is selected from one or more of sodium hydroxide, potassium hydroxide, propionic acid, acetic acid, formic acid, maleic acid, maleic anhydride, lauryl ether phosphate, coconut oil monoethanolamide, cocamidopropyl betaine and cocamidopropyl hydroxysulfonate; preferably, the pH adjuster is selected from one or more of sodium hydroxide, acetic acid and lauryl ether phosphate.

13. A texturing liquid comprising an alkali, the texturing additive composition according to any one of claims 1 to 12 and water.

14. The texturing liquid according to claim 13, in, The base is an inorganic base and / or an organic base; preferably, the inorganic base is KOH and / or NaOH, and the organic base is tetramethylguanidine and / or tetraethylammonium hydroxide.

15. The texturing liquid according to claim 13, in, The amount of the texturing additive composition is 0.05-1.5 wt %, based on the total weight of the texturing liquid; The amount of the alkali is 0.5-5.5 wt %, based on the total weight of the texturing solution.

Citation Information

Patent Citations

  • Polishing composition

    CN101821835A

  • Aqueous polishing composition and process for chemically mechanically polishing substrates for electrical, mechanical and optical devices

    CN103097476A

  • Texturing additive for preparing low-reflection solar cell and application of texturing additive

    CN118087049A

  • Silicon wafer polishing composition

    JP2020161603A

Cited By

  • Texturing agent composition and texturing liquid

    CN119980479A

  • A texturing agent composition and a texturing solution

    CN119980479B

  • Monocrystalline silicon texturing additive, preparation method thereof and texturing liquid containing monocrystalline silicon texturing additive

    CN120758976A

  • A texturing additive suitable for preparing homogeneous crack textured monocrystalline silicon and its application method

    CN122669488A

  • A texturing additive and method of use suitable for preparing uniform cleaved monocrystalline silicon

    CN122669488B